WORK MOTIVATION'S MEDIATION: TALENT AND COMPENSATION EFFECTS ON PUSKESMAS EMPLOYEE PERFORMANCE - Nugraheni, Ika Maulidia; Suryani, Tatik; Setia, Shinta (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the mediating role of work motivation in the relationship between talent management and compensation with employee performance in Community Health Center (in Indoneia terminology is called Puskesmas) in Surabaya. Using a quantitative approach and survey design, data were collected from employees of Puskesmas in the Semampir District. Statistical analysis was conducted to test the mediating effect of work motivation. The results indicate that both talent management and compensation significantly enhance employee performance, both directly and indirectly, by increasing work motivation. These findings highlight the importance of motivation as a key factor that strengthens the impact of human resource practices on employee performance. The implication of this research is that effective talent management and fair compensation systems should be prioritized by healthcare managers to improve service quality through more motivated and high-performing staff.